Research status and trends of physical activity on depression or anxiety: a bibliometric analysis - Zhang, Xin-Yue; Ye, Fang; Yin, Zi-Han; Li, Ya-Qin; Bao, Qiong-Nan; Xia, Man-Ze; Chen, Zheng-Hong; Zhong, Wan-Qi; Wu, Ke-Xin; Yao, Jin; Liang, Fan-Rong (Frontiers in Neuroscience, 2024)
Background: Anxiety and depression are prevalent mental disorders. As modern society continues to face mounting pressures, the incidence of anxiety and depression is on the rise. In recent years, there has been an increasing breadth of research exploring the relationship between anxiety, depression, and physical activity (PA). However, the current research progress and future development trends are unclear. The purpose of this study is to explore the research hotspots and development trends in this field, and to provide guidance for future studies and to provide some reference for clinicians. Methods: We searched the relevant literature of Web of Science Core Collection from the establishment of the database to August 15, 2023. CiteSpace, VOSviewer and Bibliometrix Packages based on the R language were used to analyze the number of publications, countries, institutions, journals, authors, references, and keywords. Results: A total of 1591 studies were included in the analysis, and the research in the field of PA on anxiety or depression has consistently expanded. The USA (304 publications), Harvard University (93 publications), and the journal of affective disorders (97 publications) were the countries, institutions, and journals that published the highest number of articles, respectively. According to the keywords, students and pregnant women, adult neurogenesis, and Tai Chi were the groups of concern, physiological and pathological mechanisms, and the type of PA of interest, respectively.The study of PA on anxiety or depression is experiencing ongoing expansion. Clinicians can consider advising patients to take mind-body exercise to improve mood. In addition, future researchers can explore the mind-body exercise and its impact on anxiety or depression, PA and anxiety or depression in specific populations, and adult neurogenesis of various exercise in anxiety or depression.